Zirconium in the Nuclear Industry: 18th International Symposium 2018
DOI: 10.1520/stp159720160071
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Corrosion and Hydrogen Pickup of Zirconium Fuel Cladding Alloys: The Role of Oxide Microstructure, Porosity, Suboxides, and Second-Phase Particles

Abstract: We used a range of advanced microscopy techniques to study the microstructure, nanoscale chemistry, and porosity in zirconium alloys at different stages of oxidation. Samples from both autoclave and in-reactor conditions were available, including ZIRLO™, Zr-1.0Nb, and Zr-2.5Nb samples with different heat treatments. Scanning transmission electron microscopy (STEM), transmission Kikuchi diffraction (TKD), and automated crystal orientation mapping with TEM were used to study the grain structure and phase distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 29 publications
2
16
0
Order By: Relevance
“…% and a layer thickness of about 200 nm. Similar studies on other commercial alloys corroded in pressurized water showed varying thicknesses of the same metastable ZrO suboxide at different stages of the oxidation process [12][13][14][15]. All these authors also observed an oxygen concentration gradient over a distance of 200 -400 nm into the metal from a level close to the sub-oxide of about 30 at.…”
Section: Introductionsupporting
confidence: 70%
“…% and a layer thickness of about 200 nm. Similar studies on other commercial alloys corroded in pressurized water showed varying thicknesses of the same metastable ZrO suboxide at different stages of the oxidation process [12][13][14][15]. All these authors also observed an oxygen concentration gradient over a distance of 200 -400 nm into the metal from a level close to the sub-oxide of about 30 at.…”
Section: Introductionsupporting
confidence: 70%
“…These SPPs are 20 nm to 60 nm in diameter and roughly spherical in the metallic matrix. They oxidise rapidly when incorporated into the growing oxide layer and become amorphous as previously reported [43,44], and at the same time they expand in the direction of oxidation and become elliptical in shape as oxygen atoms are incorporated ( Figure 7). In bright field TEM images, like those shown in Figure 3, SPPs can be hard to detect, but highangle annular dark field (HAADF) imaging is able to differentiate between metallic and oxidised SPPs by the change in average atomic mass (z-contrast), as seen in Figure 7.…”
Section: Second Phase Particles (Spps)supporting
confidence: 73%
“…Moving on to the h-ZrO suboxide phases at the metal-oxide interface, we have previously shown a correlation between instantaneous oxidation rate and the thickness of the combined suboxide/oxygen-saturated area layer [70]. This feature of the metal-oxide interface can be best studied by STEM HAADF and scanning precession electron diffraction mapping in the TEM, as shown in Figure 4.…”
Section: Damage To the Oxidementioning
confidence: 96%
“…The corrosion and mechanical performance of Zr alloys is intrinsically related to the nature, morphology and behaviour of second phases and the underlying microstructure [1][2][3][4][5][6][7][8][9]. It is therefore essential to characterise second phases with clarity and consistency in order to accurately assess their evolving behaviour during the lifetime of nuclear components.…”
Section: Introductionmentioning
confidence: 99%